Fiscal Multiplier in Malaysia : An Empirical Assessment and Policy Implication - Evan, Lau; Maryam, Azman; Fahrulradzi, Bukhari; Helmi, Ramlee (2022)
The concept of fiscal multiplier accounts for the impact of discretionary policy on both the shortand long-run output. While having the ability to measure the spill-over impact on growth from any fiscal measure would be critical for the formulation of fiscal policy, there are various challenges in measuring the fiscal multiplier. This paper examines the magnitude in which changes in government revenue and expenditure would affect growth, the persistency and asymmetry of these impacts for Malaysia. We find that total expenditure and total revenue induce an impact (average for the first four quarters) of 0.4 and 0.8 on growth, and these impacts are expected to be persistent up to the 20th quarter. Impact on growth is asymmetric with a positive expenditure shock, inducing the most stimulative effect while a positive revenue shock poses the largest drag on growth.